PENGARUH FINANCIAL DISTRESS DAN AUDIT TENURE TERHADAP INTEGRITAS LAPORAN KEUANGAN - Farezky Febrian Nugroho; Julian Maradina (Jurnal Nusa Akuntansi, 2026)
This study aims to determine and analyze the effect of financial distress and audit tenure on the integrity of financial reports in the property and real estate sector. Financial distress is measured using the Z-score method, and audit tenure is measured using a score of 1 = starting at the time of the engagement with the auditee, and a score of 2 = increasing annually. The data used in this study were obtained from the IDX website and the company website. This study used 28 companies in the property and real estate sector that had been eliminated according to predetermined criteria. The sampling method used was purposive sampling. The data analysis method used was panel data regression using Eviews 13.0 software. The results showed that financial distress and audit tenure simultaneously influenced the integrity of financial statements. Financial distress partially influenced the integrity of financial statements.